Preventing a biochemical arms race - Kelle, Alexander; Nixdorff, Kathryn; Dando, Malcolm (Stanford University Press, 2012)
The book analyses the revolution in the life sciences, the changing nature of warfare, and the impact of biodefense activities on the regimes to prohibit chemical and biological weapons and puts forward proposals to strengthen these regimes.